2012
DOI: 10.1159/000334100
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular and Cholangiolar Carcinoma-Derived Cell Lines Reveal Distinct Sets of Chromosomal Imbalances

Abstract: Objectives: Hepatocellular carcinoma (HCC) and cholangiolar carcinoma (CC) cell lines are used to analyze the basic mechanisms of carcinogenesis and target therapies. However, it is not yet clear which chromosomal aberrations are to be typically expected in such cell lines. It is also not clear whether there are prerequisites for in vitro growth on the genomic and/or expression level. We therefore analyzed HCC and CC cell lines for typical genetic settings. Methods: The HCC cell lines HLE, HLF, Huh7, HepG2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…22 Besides, comprehensive HCC cell lines chromosomal imbalance analysis showed that a gain of 17q, particularly 17q11, which exactly includes the SUZ12 gene locus, was seen in all examined HCC cell lines, including HepG2, Hep3B, and Huh7. 23 We also examined HCC samples and hepatoma samples metastasis from other tumors (data not shown), which further con rmed the speci cally high frequency of 17q ampli cation in HCC. (Fig.…”
Section: Suz12 Performs High Expression In Hccsupporting
confidence: 52%
“…22 Besides, comprehensive HCC cell lines chromosomal imbalance analysis showed that a gain of 17q, particularly 17q11, which exactly includes the SUZ12 gene locus, was seen in all examined HCC cell lines, including HepG2, Hep3B, and Huh7. 23 We also examined HCC samples and hepatoma samples metastasis from other tumors (data not shown), which further con rmed the speci cally high frequency of 17q ampli cation in HCC. (Fig.…”
Section: Suz12 Performs High Expression In Hccsupporting
confidence: 52%
“…One of the reasons for this could be the highly expressed phase II enzyme, Uridine 5'-diphospho-glucuronosyltransferase level in HepG2 cells, which possibly catalyze the conjugation of these compounds into hydrophilic glucuronide derivatives that might possess stronger cytotoxicity (Strassburg et al, 1998;Westerink and Schoonen, 2007). Another reason of the relatively cytotoxic resistance of HeLa and Caco-2 cells could be their aneuploid nature and chromosome instability, compared to a relatively near-diploid karyotype of HepG2 cells (Wilkens et al, 2012). Aneuploid and chromosome instability were believed to contribute to the acquisition of drug resistance by enhancing adaptation capacity to withstand cellular stresses (Lee et al, 2011;McClelland et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Hep3B cells (hepatoma cells with a ploidy status of n = 3.2, see Wilkens et al 95 ; for mutations in cancer genes see Table S1 in Ewald) 96 were plated in 6-well plates in complete medium and transfected with a linearized plasmid containing the STAT3-inducible promoter rPAP1 35,36 in front of the secreted Cypridina luciferase gene, using the PromoFectin-Hepatocyte reagent (PromoCell, Bio-Connect, Huissen, the Netherlands), following the manufacturer's protocol. 4 h later, serum-reduced Optim-MEM medium (Life Technologies, Merelbeke, Belgium) was replaced by normal DMEM.…”
Section: Materials and Cell Culturementioning
confidence: 99%